2003
DOI: 10.1038/sj.ejcn.1601643
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bioelectrical impedance analysis and dual-energy X-ray absorptiometry for the assessment of appendicular body composition in anorexic women

Abstract: Objective: To establish the accuracy of bioelectrical impedance analysis (BIA) for the assessment of appendicular body composition in anorexic women. Design: Cross-sectional study. Setting: Outpatient University Clinic. Subjects: A total of 39 anorexic and 25 control women with a mean (s.d.) age of 21 (3) y. Methods: Total, arm and leg fat-free mass (FFM) were measured by dual-energy X-ray absorptiometry and predicted from total and segmental BIA at 50 kHz. The predictor variable was the resistance index (Rl),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…The limits of agreement of FFM estimates obtained from ZI 100 were two times wider in males (À12.2 to 12.2 kg) than in females (À6.8 to 6.8 kg) and in both cases there was evidence of negative proportional bias. As we have observed in many of our studies of four-polar BIA (Bedogni et al, 2003), weight was more accurate than ZI at predicting FFM. The only advantage of the combination of weight and ZI 100 was a modest decrease of the bias in females (from À5.6 to 5.6 kg to À5.0 to 5.0 kg).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The limits of agreement of FFM estimates obtained from ZI 100 were two times wider in males (À12.2 to 12.2 kg) than in females (À6.8 to 6.8 kg) and in both cases there was evidence of negative proportional bias. As we have observed in many of our studies of four-polar BIA (Bedogni et al, 2003), weight was more accurate than ZI at predicting FFM. The only advantage of the combination of weight and ZI 100 was a modest decrease of the bias in females (from À5.6 to 5.6 kg to À5.0 to 5.0 kg).…”
Section: Discussionsupporting
confidence: 71%
“…Selection of variables for FFM prediction algorithms was carried out by stepwise bootstrapped linear regression on 1000 random samples of 68 subjects (Harrell, 2001). Candidate predictors were gender, age, weight and ZI at frequencies of 5, 50 and 100 kHz (Bedogni et al, 2003). Predictors identified at bootstrap analysis were entered into multiple regression models with standard errors of coefficients calculated by bootstrap analysis on 1000 random samples of 68 subjects (Gonçalves and White, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous research performed in adults, we have consistently found that RI8 contributes more than weight to the prediction of total body water, extracellular water and FFM (Bedogni et al, 2002(Bedogni et al, , 2003aMalavolti et al, 2003;Medici et al, 2005), contrarily to what happens for RI4 (Bedogni et al, 2003b;Bertoli et al, 2007). The analysis of the KISS data confirms that weight contributes more than RI4 and less than RI8 to the prediction of FFM in young children.…”
Section: Discussionsupporting
confidence: 53%
“…An octopolar (8-BIA) multifrequency implementation of BIA with tactile electrodes was recently made available on the market (Bedogni et al, 2002). Contrarily to 4-BIA (Bedogni et al, 2003b;Bertoli et al, 2007), 8-BIA was consistently found to contribute more than anthropometry to the prediction of body composition (Bedogni et al, 2002;Malavolti et al, 2003;Medici et al, 2005). However, 8-BIA has not been directly compared to 4-BIA and has been validated only for selected physiological and clinical conditions (Bedogni et al, 2002;Malavolti et al, 2003;Medici et al, 2005;Sartorio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We have the policy of systematically testing this hypothesis in our BIA studies. For instance, we have not been able to show that four-polar BIA at 50 kHz is more accurate than Wt in estimating TBW and appendicular body composition in anorexic women (Scalfi et al, 1997;Bedogni et al, 2003b). Even if the use of multifrequency instruments may change this evidence, the use of an impedance-meter is clearly not justified in these circumstances.…”
Section: Discussionmentioning
confidence: 74%